Sustainable Development Governance from Margins to Mainstream: Overcoming Traps by Embracing Complexity - Monaco, Edoardo (European Journal of Sustainable Development, 2018)
The present essay reflects on the significances of a major turning point in global sustainable development governance: the adoption by the United Nations of the “2030 Agenda for Sustainable Development”. The Agenda and its seventeen “Sustainable Development Goals” (SDGs) authoritatively redefine the very concept of development, as holistic synthesis of long-term achievements in the interconnected domains of society, politics, economics and environment. As a consequence, new, comprehensive metrics – quantitative and qualitative in nature - are required, so as to measure the pursuit of this new, complex form progress. While it appears important to overcome approaches that aim exclusively at unconditional market output maximization, economic growth remains, at this point, central to any development design. Yet, qualitative considerations about growth are, in a sustainable framework, now in order more than ever: in particular, factors such as diversity of productive know-how and economic inclusion matter greatly, as the observation of global development patterns over time demonstrates. Fundamentally, the 2030 Agenda calls for a paradigmatic shift investing all components of society – from citizens to governments, corporations, academics, media - and possibly challenges the very nature and content of the traditional social contracts that govern them. Keywords: sustainable development; 2030 Agenda; SDG; complexity; quality; diversity.